Characterization of Plasma Cell-Free DNA Integrity Using Droplet-Based Digital PCR: Toward the Development of Circulating Tumor DNA-Dedicated Assays - Poulet, Geoffroy; Garlan, Fanny; Garrigou, Sonia; Zonta, Eleonora; Benhaim, Leonor; Carrillon, Marie-Jennifer; Didelot, Audrey; Le Corre, Delphine; Mulot, Claire; Nizard, Philippe; Ginot, Frederic; Boutonnet-Rodat, Audrey; et al. (Frontiers in Oncology, 2021)
BACKGROUND: ccfDNA is being explored as a diagnostic and prognostic tool for various diseases including cancer. Beyond the evaluation of the ccfDNA mutational status, its fragmentation has been investigated as a potential cancer biomarker in several studies. However, probably due to a lack of standardized procedures dedicated to pre-analytical and analytical processing of plasma samples, contradictory results have been published. METHODS: ddPCR assays allowing the detection of KRAS wild-type and mutated sequences (KRAS p.G12V, pG12D and pG13D) were designed to target different fragments sizes. Once validated on fragmented and non-fragmented DNA extracted from cancer cell lines, these assays were used to investigate the influence of the extraction methods on the non-mutated and mutated ccfDNA integrity reflected by the DII. The DII was then analyzed in two prospective cohorts of metastatic colorectal cancer patients (RASANC study n = 34; PLACOL study n = 12) and healthy subjects (n=49). RESULTS & DISCUSSION: Our results demonstrates that ccfDNA is highly fragmented in mCRC patients compared to healthy individuals. These results strongly suggest that the characterization of ccfDNA integrity hold great promise toward the development of a universal biomarker for the follow-up of mCRC patients. Furthermore, they support the importance of standardization of sample handling and processing in such analysis.